Transformasi Mahkamah Syariah di Malaysia: Keperluan Kajian Semula Terhadap Bentuk Hukuman Bagi Kes-Kes Jenayah Syariah - Jasri Jamal; Hasnizam Hashim (Universiti Sains Islam Malaysia, 2024)
This article discusses on the need to transform and diversify the forms of punishment in the Syariah Court. The Syariah Court Act (Criminal Jurisdiction) 1965 (Amendment 1984) [Act 355] provides that Syariah Court could inflict a maximum of RM5000.00 fine, maximum of 3 years imprisonment or 6 lashes or combination thereof all of which fall under Takzir category; legislated by the government for the Syariah Criminal cases. These provisions have been in use for over 35 years in Malaysia without any modifications. In Islamic Fiqh, the law related to Takzir must always be reviewed to ensure that it relevant to suit with current problems of the society and the nation.